Evaluation of smear layer removal after use of a canal brush: an SEM study - SAZAK ÖVEÇOĞLU, HESNA; GÜNDAY, MAHİR (MOSBY-ELSEVIER, 2010)
Objective. The objective of this study was to evaluate smear layer removal after using the new CanalBrush (Coltene/Whaledent GmbH+Co. KG, Germany). Study design. Twenty extracted maxillary anterior teeth were randomly divided into 2 equal groups. The canals of the teeth in each group were instrumented with ProTaper Universal rotary files (Dentsply Maillefer, Switzerland). Following each file use, the root canals in both groups were irrigated with 5.25% NaOCl and 15% EDTA. At the end of instrumentation, the canals in group 2 were flushed with 15% EDTA, then a CanalBrush was used for 30 seconds, and a final irrigation was conducted with 5.25% NaOCl. All teeth were processed for scanning electron microscopy (SEM), and the removal of the smear layer was examined in the apical, middle, and coronal thirds. Analyses of SEM images were performed by 2 independent evaluators in a blinded manner and using a 4-point scoring system. Results. The middle and apical thirds of the root canals in group 2 showed lower average scores than those in group 1, but the difference was not statistically significant. There was no significant difference in the coronal score between the groups (P>.05). Conclusions. Irrigating with brushing tended to produce cleaner canal walls, but irrigating brushing was not significantly better than irrigation alone in removing the smear layer on the canal walls. (Oral Surg Oral Med Oral Pathol Oral Radiol Endod 2010;110:e62-e66)
Keywords: SCANNING-ELECTRON-MICROSCOPE; EFFICACY; EDTA; IRRIGANTS; DEBRIS; TEETH